MANAGING RAPPORT ON SOCIAL MEDIA: THE EFFECTIVENESS OF RAPPORT MANAGEMENT STRATEGIES TO MITIGATE RAPPORT THREATENING BEHAVIORS IN SOCIAL MEDIA INTERACTIONS - Reski, Reski; Nugroho, Dwi Adi; Sudewi, Putu Wahyu; Asdar, Asdar; Rusdiah, Rusdiah (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2024)
his study aims to find out the rapport management strategies to mitigate rapport threatening behaviors in social media interactions and to find out the effectiveness of the strategies. The social media platform from which the data was obtained is Facebook. There are a number of rapport threatening behaviors on the social media platform which are insult, criticism, cynicism, mockery, profanity, accusation, challenge, and blasphemy. These acts and expressions are considered to be threats to rapport since they can cause verbal conflicts and dispute in the interactions. This study found that these threats can be mitigated by rapport management strategies which comprise of five types of domains. This study, however, only found three domains of strategies and one newly found strategy in social media context. Most of the strategies are evidently effective to mitigate the rapport threats and consequently maintain the harmonious situation of the social media interactions